Shallow Foundation Stability on Expansive Clay Using Group Granular Pile Anchor - Alvin John Lim Meng Siang; Ehab Hamad Sfoog; Nickholas Anting Anak Guntor; Mohd. Hidayat Rabon (International Journal of Integrated Engineering, 2026)
Expansive soil is problematic because it undergoes significant volume changes due to its tendency to swell when it absorbs moisture and shrink when it dries out. This characteristic can lead to serious structural issues for buildings, roads, and other infrastructure. The solution for this problem is to use a Granular Pile Anchor (GPA) system, an innovative foundation technique that uses a steel anchor extended from a shallow foundation and embedded into a granular pile at depths below expansive soil layers. This enhances the load-bearing capacity, providing additional resistance to uplift forces or lateral loads on expansive soil. The effectiveness of GPA in overcoming uplift forces on structures can be further improved by studying its optimum design. Therefore, this research studies a comprehensive design by incorporating a group pile system on the GPA compared to varying steel anchor lengths and diameters in mitigating heaving using a 3D finite element software PLAXIS. Heave and uplift forces reduction was obtained through varying dimensional input parameters from the ratio of GPA length to the expansive soil layer thickness (L/H), the area replacement ratio (Ar), which is the ratio of the foundation footing area to GPA cross-section area, and the number of group GPA (N). The results indicated that with L/H = 1.5, where the length of GPA extends partly in the expansive soil, and N = 3, the heave and the uplift forces were reduced to 92.55% and 92.79%, respectively. These improvements were sufficient for the optimum performance of the GPA structure. This indicates the vast improvements in the performance of the shallow foundation to mitigate heaving problems due to expansive soil with the application of group GPA.